PENGARUH MANAJEMEN LABA AKRUAL DAN AKTIVITAS MANAJEMEN LABA RIIL TERHADAP KINERJA PERUSAHAAN - Heni Yusnita; M. Mulyadi; E. Erick (JAFFA, 2015)
This research aims at identifying firm’s tendency to execute earnings management throught accruals and real earnings management and its impact to firm performance. This study uses data from 46 manufacturing companies listed in Indonesia Stock Exchange during 2010 to 2013. Accrual earnings management is measured by discretionary accruals based on modified Jones model’s (1991), whereas real earnings management used is based on the Roychowdhury model’s (2006), there is real earnings management through operating cash flow and production costs . Firm performance is measured by Tobin’s q. Then, testing of hypotheses to analized impact of earnings management on firm performance using multiple regression analysis.The results show that the manufacturing companies listed in Indonesia Stock Exchange tend to execute accruals earnings management and real earnings management throught the operating cash flow and production cost. Moreover, accruals earnings management and real earnings management through operating cah flow and production costs effect firm performance. The research is expected to be information for business people about the existence of accrual earnings management and real earnings management and its impact to firm performance, so it can be a consideration in making investment decisions. Keywords: accrual earnings management, real earnings management, Tobin’s q